METODE DEMONSTRASI UNTUK MENINGKATKAN KEMAMPUAN PEMBELAJARAN ILMU PENGETAHUAN SOSIAL ( I P S ) SISWA KELAS III SD NEGERI 008 RAMBAH SAMO KECAMATAN RAMBAH SAMO, KABUPATEN ROKAN HULU - N I R Y A N D I, N I R Y A N D I (EDUTECH CONSULTANT, 2017)
Demonstration Method To Improve Learning Ability Social Science For Student Third Class Sekolah Dasar Negeri 008 Rambah Samo, Kabupaten Rokan Hulu. Demonstration method was a how to teach with to show a object or behavior can be give description about meaning ability human to act. This method can to improve ability of social science third class of SD Negeri 008 Rambah Samo, this proved after to do learning with the method the student interesting in learning. And can be to reveal their opinion and can to find creativity to study. In use this method writer still consider the time, condition of student, a problem to identification before to do this classroom action research, so that right in taking action, proved to be an increase in a row-succession from cycle I meeting I with the cycle II meeting II learning was success. This method can to do with the problem identification, formulation of the problem, to plan, to do act, and to evaluation. So that can be success to improve student achievement.